2013
DOI: 10.1155/2013/524894
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the Quality of Life in Patients with Multiple Sclerosis in Clinical Practice: A Necessary Challenge

Abstract: While the physical disability aspect of multiple sclerosis (MS) is of great importance, quality of life (QoL) measurements are being considered increasingly important with regard to evaluating disease progression, treatment, and the management of care provided to MS patients. Despite the acknowledged need to consider QoL issues, QoL assessment remains underutilized in clinical practice. These issues should be explored and understood to promote the use of measuring QoL in MS clinical practice. We explore the di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
68
0
6

Year Published

2014
2014
2017
2017

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 87 publications
(74 citation statements)
references
References 96 publications
0
68
0
6
Order By: Relevance
“…Caractéristiques de l'échantillon Nos hypothèses ont été formulées dans une perspective théra-peutique, afin de déterminer si la prise en charge des faibles niveaux d'estime de soi pouvait améliorer de façon significative les troubles dépressifs et les troubles anxieux [3][4][5] qui, à leur tour, pouvaient conduire à une amélioration de la qualité de vie [16,17]. Nous avons également testé dans ce modèle l'influence du niveau du QI.…”
Section: Résultatsunclassified
“…Caractéristiques de l'échantillon Nos hypothèses ont été formulées dans une perspective théra-peutique, afin de déterminer si la prise en charge des faibles niveaux d'estime de soi pouvait améliorer de façon significative les troubles dépressifs et les troubles anxieux [3][4][5] qui, à leur tour, pouvaient conduire à une amélioration de la qualité de vie [16,17]. Nous avons également testé dans ce modèle l'influence du niveau du QI.…”
Section: Résultatsunclassified
“…Although, recent studies reported data providing strong arguments to support the conclusion that patients with cognitive dysfunction are reliable and consistent when answering a QoL questionnaire. These works suggested that cognitive dysfunction did not compromise the reliability or validity of the selfreported QoL questionnaires among subjects with cognitive dysfunction and clarify the relevance of using self-reported QoL assessments in clinical practice (12,65,66).…”
Section: Quality Of Life Evaluation For Individuals With Cognitive Immentioning
confidence: 94%
“…Many questionnaires, specific and generic, are proposed to assess QoL. Generic instruments are generally used to compare QoL across different populations, while disease-specific instruments focus on particular health problem and seem more sensitive for detecting changes (12,13).…”
Section: A Large Variety Of Quality Of Life Instrumentsmentioning
confidence: 99%
“…Several studies have investigated the effects of disability on the quality of life in multiple sclerosis patients (3,5,(21)(22)(23)(24)(25); for example, Pfaffenberger et al showed that the levels of physical and mental disability have significant effects on the quality of life (3). These findings were confirmed by the results of Miller and Dishon (24).…”
Section: Relationship Between Disability and The Quality Of Lifementioning
confidence: 99%